Leadership in education - Brundrett, Mark; Burton, Neil, 1960-; Smith, Robert, 1944- (London : Sage Publications, 2003)
Leadership in learning-centered schools: cultural context, functions and qualities -- Leadership's places in a community of practice -- Gender in educational leadership- - Biography and the study of school leader careers: towards a humanistic approach - - Models of leadership development; learning from international experience and research - - The National College for School Leadership: its role in developing leaders - -Teacher leadership: its nature, development, and impact on schools and students - - Teacher leadership: prospects and possibilities - -Effective leadership for war and peace - -Leading high - -performing schools - - Leadership in further education - -Leadership in UK higher education
Includes bibliographical references and index
Keywords: Educational leadership -- Great Britain